Cost-Effective Stator Modification Techniques for Cogging Torque Reduction in Axial Flux Permanent Magnet Machines - Kumar P.; Srivastava R.K. (My University, 2025)
Cogging torque reduction in permanent magnet machines is an important issue as it leads to output torque ripple, vibrations and noise. Several techniques are available for cogging reduction in radial flux machines. Out of them, the various rotor modification techniques are directly applicable to axial flux machines. However, the stator modification techniques cannot be directly applied due to difficulty in punching slots in axial stator laminations leading to high cost. This paper discusses some design techniques which can be easily implemented and are also cost-effective. A 3-D Finite Element model of an Axial Flux Permanent Magnet (AFPM) machine with various modifications is simulated. It is found that a maximum reduction of 98.71 % in cogging torque was obtained by opposite skewing of the successive slot-openings as compared to a parallel-tooth open-slot machine. The various results were obtained using Finite Element based simulations. © 2018 IEEE.